Factors Affecting the Decision to Use Products within the UOB Bank in the Bangkok Area - Jaroenprasitthisuk, Werathana; Chuacharoen, Orathai (Rajapark Journal, 2024)
This research aims to investigate the factors influencing the selection of products within the UOB bank in the Bangkok area. The sample population consists of 400 individuals surveyed through Google Forms, with questions covering personal factors, consumer behavior (6W1H), the 7Ps of marketing, and decision-making. This quantitative research collected and analyzed data using statistical methods, summarizing the findings with inferential statistics. The statistics used were descriptive, correlation tests, and regression analysis. The abstract outlines three main points: 1. Demographic factors such as gender, age, marital status, occupation, and monthly income significantly influence product selection within UOB bank branches in Bangkok. 2. Different levels of education do not significantly impact the decision-making process regarding product selection within UOB bank branches in Bangkok, both overall and in specific aspects such as problem recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. 3. Marketing mix factors (7Ps), specifically distribution channels (place), promotional activities (promotion), and physical evidence, significantly influence product selection decisions within UOB bank branches in Bangkok at a statistically significant level of 0.05.